Improving the implementation of Indonesian halal logistics: a statistical approach - Kurniawati, Dwi Agustina; Kristanto, Dwi; Zailani, Suhaiza; Rochman, Muhammad Arief; Caroline, Cindy (SINERGI, 2025)
In Indonesia, only a limited number of logistics providers have obtained halal certification, even though halal logistics plays a crucial role in preserving product integrity and preventing cross-contamination. This study analyzes the implementation of halal logistics by identifying key variables that influence the availability of halal products in the Indonesian market. Using a quantitative research approach, data were collected through surveys of 108 companies, including 35 logistics service providers and 73 halal-certified MSMEs, as well as semi-structured interviews with logistics service providers and MSME business actors in the food sector. The data were analyzed using multiple regression analysis to determine the most influential factors affecting halal product availability. The findings indicate that halal product information availability, consistent worker training, and corporate environmental responsibility are the primary variables influencing halal product availability. These insights provide a foundation for policymakers to develop regulations that strengthen halal logistics while enabling logistics providers and MSMEs to allocate resources more effectively to maintain halal product availability in the market. As one of the few studies examining halal logistics in Indonesia’s food sector, this research contributes to the broader discourse on halal supply chain management and policy development. This study emphasizes the need for stronger stakeholder collaboration to enhance halal logistics sustainability in Indonesia.